Development of speed, agility and strength in middle school students - Mihai ȘANDRA; Cristina Nicoleta ABODI; Gheorghe Codruț BULZ; Tudor CACIORA; Marius Alin MARINĂU (Editura Universităţii din Oradea, 2023)
Physical education is the discipline in the school curriculum that can help in different ways to educate and train children, young people and adults, contributing to personal and professional development but also the activity through which the subject, performing physical activities, becomes aware of his possibilities, in the conditions of success or failure , in the struggle with oneself or with others, learning at the same time to know oneself better and to know the world better. In the current conception, physical education and school sports constitute one of the most important links of physical education. Due to the fact that students in this educational cycle enter a stage of their lives characterized by profound morpho-functional, motor and psychic transformations, their interest in movement is very high during this period. The present study aims to develop speed, agility and strength, within the physical education lesson, aiming to maximize specific means. The experiment includes the two groups, control and experiment, thus following the interpretation of the results, the progress or regression of the experimental group will be more obvious and easy to analyze, thus the subsequent decisions regarding the content of the subsequent program being simpler, following the previous evaluation. The physical education of the last period suffers in terms of planning and organization of the proposed ones, and through the present paper we highlight the fact that through a correctly carried out activity, positive results appear.